Characterization of Eggshell and Natural Chloride Stabilized Soil Using Geophysical Techniques - Kumar, Amit; Soni, Dharmender Kumar (International Journal of Integrated Engineering, 2021)
Although many techniques are available for the evaluation of soil parameters, but a quick and efficient method is always welcome. To avoid the hassle calculation and tedious procedures of testing; practitioners seek a fast method for site implementation of laboratory results. In the recent era of development and technology, it has been necessary to adopt the advanced techniques to evaluate the geotechnical parameters. In the present study, correlations between Ultrasonic Pulse Velocity (UPV) and Maximum Dry Density (MDD); Electrical resistivity (Re) and Optimum moisture content (OMC) were derived. In the present study eggshell powder (ESP) as a waste material was used along with sodium chloride (NaCl) and polypropylene fiber (PPF) to stabilise the soil. Design of experiments was done by Taguchi technique using Minitab 17 software. A series of non-destructive UPV and Re tests was carried out on 21 days aged soil specimens. Results found ESP as the dominating factor, for attaining improvement in packing of soil particles and make soil resistive. The utility of the present study can be found in places where dense soil and electric resistive properties meets such as transmission lines and railway electric poles etc.